THE ROLE OF THE URBAN ENVIRONMENT IN IMPLEMENTING THE CIRCULAR ECONOMY IN ROMANIA - Danu, Cornelia Marcela; Nechita, Elena; Manea, Liliana Rozemarie (Studies and Scientific Researches. Economics Edition, 2015)
In the present paper we analyzed the position of the Romanian urban environment in the process of implementing the circular economy, with the correlations and interdependences between the phenomena and demo-economic processes and the forms for the application of the circular economy. The poor implementation of the circular economy in the urban areas in Romania is conditioned by the low level of income, the expenditure, the consumption expenditure and the degree of low urbanization, the low level of labour productivity, etc., and by the psychology of the decision makers that is still not adjusted to the requirement to make the best choices for sustainable development of the economic system. We have highlighted the correlations between: the municipal waste recycling rate and the resource productivity in Romania; the total income of the population in the urban areas of residence in Romania and the waste recycling rate; the total average expenditure per person in urban areas and the municipal waste recycling rate; the monthly average consumption expenditure per person, in urban areas and municipal waste recycling rate; the employed population rate in urban areas and the municipal waste recycling rate; the urban population living in the 41 counties of Romania and Bucharest and the municipal waste recycling rate.